Contraceptive and abortion practices of young Ghanaian women aged 15-24: evidence from a nationally representative survey - Sarah C. Keogh; Easmon Otupiri; Philicia W. Castillo; Naomi W. Li; Joana Apenkwa; Chelsea B. Polis (BMC, 2021)
Plain English summary Young Ghanaian women can experience difficulties accessing sexual and reproductive health services, and many are not using contraception despite wanting to avoid pregnancy. To better understand their needs, we describe their preferences and behaviors around contraception and abortion. We surveyed a nationally representative sample of women aged 15-49, and compared young (15-24) versus older (25-49) women's contraceptive preferences, reasons for stopping contraception, quality of counseling, friends' and partners' influence on contraceptive use, and use of abortion. One-third of 15-24 year-olds who ever had sex were using contraception. Compared to older women, young women's pregnancies were more likely to be unintended and to end in abortion. Young women most commonly used condoms, injectables, withdrawal or implants; and were more likely than older women to use condoms, withdrawal, emergency contraception, and Primolut N-tablet. They preferred methods that were effective, did not harm their health or future fertility, were easy to use, and did not disrupt their menstrual cycle. Over half of young women who stopped contraception did so because they were not having sex regularly. Friends had more influence on contraceptive use among young women than older women. Each year on average, there were 30 abortions per 1000 young women. Over half of young women who had abortions used methods from non-formal providers, and 40% of those who had complications did not get treated. Providers should be equipped to provide confidential, non-discriminatory counseling about contraceptive side effects and options. Social networks can be used to educate women about safe abortion.